OPINIONS AND CONSTRAINTS FACED BY FARMERS IN MAINTENANCE OF TANKS UNDER MISSION KAKATIYA - D. SRINIVASA CHARY, SALLA SOWJANYA, R. VIJAYA KUMARI, T. LAVANYA, ALDAS JANAIAH, SEEMA and (The Journal of Research, PJTSAU, 2020)
The objective of the study was to record and document the opinions of the sample farmers on advantages and disadvantages of Mission Kakatiya, and factors that influence their participation and non-participation in tank maintenance activities after restoration. In Telangana state one tank each in Warangal and Nalgonda districts i.e a total of two tanks where in all the activities of Mission Kakatiya were completed were purposively selected for the present study. A total of 720 households (360 from each district) were considered. Descriptive analysis and Garrett ranking technique were used to analyse the present study. The study revealed that,100 percent of sample farmers opined that the yield was increased and FYM usage was reduced after application of silt in their fields. 86.19 percent of silt applied sample farmers opined that the number of irrigations were reduced. Cent percent of the tank area farmers opined that the major advantages of Mission Kakatiya are increased ground water level, water availability for irrigation, birds and livestock, increased animal grazing hours and crop yields. Cent percent of the farmers opined that there were no disadvantages of Mission Kakatiya and felt that the restored tank has to be conserved. Availability of irrigation water was found to be the most important factor influencing sample farmers to participate in tank maintenance activities, ranked first. The most important reason for factors influencing non-participation in tank maintenance activities is expecting government to do repairs and maintenance was ranked first. The opinion on benefits of restoration of tanks by sample farmers in non-tank areas was found to be increase in ground water recharge (first rank).